Serotype Distribution and Antimicrobial Sensitivity Profile of Streptococcus pneumoniae Carried in Healthy Toddlers before PCV13 Introduction in Niamey, Niger. - Sani Ousmane; Bouli A Diallo; Rasmata Ouedraogo; Abdel-Kader A Sanda; Amadou M Soussou; Jean-Marc Collard (PLoS ONE, 2017)
BACKGROUND:To mitigate the burden of pneumococcal infections in Niger, a 13-valent pneumococcal vaccine, PCV13, was introduced for routine child vaccination in July 2014. In order to provide pre-vaccine baseline data and allow appreciation of changes on carriage due to vaccination, we analyzed retrospectively pneumococcal isolates obtained from healthy, 0 to 2 year old children prior to the vaccine introduction. METHODS:From June 5, 2007, to May 26, 2008, 1200 nasopharyngeal swabs were collected from healthy 0 to 2 year old children and analyzed by standard microbiological methods. Serotyping was done by SM-PCR and the data were analyzed with R version 2.15.0 (2012-03-30). RESULTS:Streptococcus pneumoniae was detected in 654/1200 children (54.5%) among whom 339 (51.8%) were males. The ages of the study subjects varied from few days to 26 months (mean = 7.1, median = 6, 95% CI [6.8-7.4]). Out of 654 frozen isolates, 377 (54.8%) were able to be re-grown and analyzed. In total, 32 different serogroups/serotypes were detected of which, the most prevalent were 6/(6A/6B/6C/6D) (15.6%), 23F (10.6%), 19F (9.3%), 14 (9%), 19A (5.6%), 23B (4.0%), 25F/38 (3.7%), 18/(18A/18B/18C/18F) (2.9%) and PCR non-typeable (16.4%). Eleven serogroups/serotypes accounting for 57.3% (216/377) were of PCV13 types. Of the 211/377 (56%) isolates tested for drug sensitivity, 23/211 (10.9%), 24/211 (11.4%), 9/211(4.3%) and 148/210 (70.5%) were respectively resistance to oxacillin, chloramphenicol, erythromycin and tetracycline. Thirteen of the oxacillin resistant isolates were additionally multidrug-resistant. No resistance was however detected to gentamycin500μg and to fluoroquinolones (ø Norfloxacin5μg <7mm). Age > 3 months and presence in family of more than one sibling aged < 6 years were significant risk factors for carriage. CONCLUSION:A global rate of 54.5% pneumococcal carriage was detected in this study. The introduced PCV13 vaccine should cover 57.3% (216/377) of circulating serogroups/serotypes, among which were those resistant to antibiotics. Age > 3 months and presence in family of children aged < 6 years were significant factors for pneumococcal carriage. The present data should help understanding post vaccine introduction changes in pneumococcal carriage and infections for better action.